Political Will Kementerian Pariwisata dan Ekonomi Kreatif Dalam Memulihkan Ekonomi Negara di Era Pandemi - Dimas Rangga Agustin; Hanny Purnamasari; Kariena Febriantin (Peneliti.net, 2022)
A pandemic is a time when the world is in crisis, especially health and the economy. In addition to being faced with a health crisis, Indonesia is also facing an increasingly unhealthy economic condition. The sectors that have the most influence on the country's economy are the tourism sector and the creative economy. In this case, the ministry of tourism and creative economy (Kemenparekraf) is the institution that bears the duties and authorities. In this study, the researcher tries to explain in terms of the political will of the government, especially the Ministry of Tourism and Creative Economy in an effort to restore the country's economy in the pandemic era. The method used in this research is descriptive qualitative with a literature/literature study approach. The results and discussion in this study are based on Brinkerhoff's theory of political will which has 7 (seven) indicators in describing the organization's/government's efforts in providing political influence and creating public confidence in the government